Peningkatan Mutu Pendidikan Sebagai Daya Tarik Sekolah Melalui Implementasi Merdeka Belajar P5 - Febriyanti, Salsabilla; Ainun Nadlif (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
The purpose of this study is to determine the current state of society's attraction to the quality of education, especially in relation to the introduction of autonomous learning. Descriptive qualitative research is the methodology used in this study, and data were collected through literature review, interviews, and observations. We can conclude that the implementation of autonomous learning can help to appreciate the importance of education quality in attracting public attention and fostering public trust in educational institutions. The main purpose of this autonomous learning policy is to offer suggestions for improving teaching standards in Indonesia, focusing on the curriculum, teaching force and learning outcomes. By integrating character values, raising teaching standards, and improving the learning environment, the Pancasila Student Project (P5) significantly improves the quality of education. P5 supports a holistic approach that combines academic achievement with the development of character and social skills, creating more engaging and quality schools. By involving all stakeholders and utilizing evaluation and feedback, P5 can continue to adapt and evolve, meeting the dynamic needs of education and supporting the formation of a better future generation.